Does B Cell Follicle Exclusion of CD8+ T Cells Make Lymph Nodes Sanctuaries of HIV Replication? - Beck, Sarah E.; Veenhuis, Rebecca T.; Blankson, Joel N. (Frontiers in Immunology, 2019)
As we learn more about the HIV latent reservoir, we continue to discover that the viral reservoir is more complicated than just a pool of infected resting memory CD4+ T cells in peripheral blood. Evidence increasingly points to both certain tissues and certain types of cells as potential viral reservoirs. T follicular helper cells (TFH) are prime targets of HIV infection—this creates a sanctuary for infected cells because CD8+ T cells generally do not enter lymph node follicles unless they express CXCR5, and are not as effective at killing infected CD4+ T cells as peripheral CD8+ T cells. In this review, we summarize the current state of research on TFH cell infection in peripheral lymphoid tissues and focus on the question of whether CD8+ T cell exclusion from B cell follicles is responsible, at least in part, for establishing secondary lymphoid tissue B cell follicles as an anatomic site of HIV transcription and replication.